(untitled) - FOS (Illinois, 1993)
This book describes approved methods of repairing fiberglass reinforced plastic parts. Fiberglass Reinforced Plastic (FRP) is an integral part of modern machine structures such as automobile bodies, light airplanes, boats, outdoor power equipment and agricultural machinery that require body strength and lightweight structural features. FRP is a composite material, a combination of flexible "fibrous glass" strands, bonded together with plastic "resin"
Keywords: agricultural mechanics